European Wool Carder Bee, Wool Carder Bee Anthidium manicatum (Insecta: Hymenoptera: Megachilidae) - Samantha Gallagher; Andrea Lucky (EDIS)
The European wool carder bee Anthidium manicatum (Linnaeus) is a solitary, cavity-nesting bee species in the family Megachilidae (tribe Anthidiini), a family whose members include the mason and leaf cutter bees. Wool carder bees are so named because the female bee scrapes and collects the soft downy hairs (trichomes) of fuzzy plants to use in building a nest for her young. Some consider male wool carder bees very charismatic and enjoy watching them chase after other bees that invade their territory, while others would call them bullies based on male bees’ aggressive tendencies toward other bees when defending floral resources.